Development of PowToon-Based Physics Learning Media on Atomic Nucleus Materials for Class XII Senior High School - M Nor; Mitri Irianti; Suci Dilla Melani (Program Studi Pendidikan Fisika FKIP Universitas Riau, 2021)
Online service in the form of the Powtoon application can be used to develop physics learning media with presentations that have very interesting animation features. The purpose of this research is to produce a learning media product in the form of a compact disk (CD) on the subject of the atomic nucleus in the learning process of class XII high school students. The research method uses Research and Development with the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation) which is modified only to the development stage. Based on the results of the validation test on the content aspect obtained 90%, the design aspect 83%, the pedagogic aspect 87%, and the ease of use aspect 84%. The results of this research indicate that the learning media using the Powtoon application on the atomic nucleus material is declared valid. Thus the Powtoon application-based learning media is declared feasible to be used as a learning media on atomic nucleus material in class XII SMA.